Restoration of Height after 11 Years of Letrozole Treatment in 11 beta-Hydroxylase Deficiency - BEREKET, ABDULLAH; BUĞDAYCI, ONUR; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (KARGER, 2020)
11 beta-hydroxylase deficiency (11 beta-OHD) is the second most common form of congenital adrenal hyperplasia (CAH). Males with 11 beta-OHD CAH are often diagnosed late with a significantly advanced bone age leading to a poor height prognosis due to early closure of epiphysis. Delaying epiphyseal fusion by treatment of aromatase inhibitors (AIs) might be a useful strategy in patients with very advanced bone ages. However, there are limited data regarding the effect on final height and long-term safety of this approach. We report our experience with 11 years of letrozole treatment and 17 years of follow-up in a boy with 11 beta-OHD. He presented at 2 years and 11 months of age with a bone age of 13 years (predicted adult height, PAH, 129.5 cm). Letrozole was added after 1 year of glucocorticoid treatment due to no improvement in height prognosis (130 cm), and continued until the age of 14 years and 11 months. He also received GnRH analog treatment at 10 years and 3 months of age for 2.5 years due to central activation of puberty. He reached a final height of 165.2 cm (35.2 cm above his PAH). This long-term treatment with letrozole was associated with changes in vertebral morphology such as vertebral body end-plate changes, Schmorl nodes, and mild protrusions in the intervertebral discs. Testicular volumes, gonadotropins, testosterone, and anti-Mullerian hormone were normal at age 20 years. A spermiogram showed a normal count but impaired sperm motility and morphology. This unique case represents the longest duration of AI treatment reported in CAH and the first case in which letrozole was started before puberty with the final height reported. We conclude that AIs may restore height in selected patients with CAH with very advanced bone age and severely compromised height prognosis.
Keywords: Letrozole; Congenital adrenal hyperplasia; Short stature; Advanced bone age; 11 beta-hydroxylase deficiency; Aromatase inhibitors; CONGENITAL ADRENAL-HYPERPLASIA; IDIOPATHIC SHORT STATURE; PREDICTED ADULT HEIGHT; AROMATASE INHIBITOR; CONSTITUTIONAL DELAY; PRECOCIOUS PUBERTY; GROWTH VELOCITY; FINAL HEIGHT; BOYS; ANASTROZOLE